The BRCA2 polymorphic stop codon: stuff or nonsense? - Higgs, J E; Harkness, E F; Bowers, N L; Howard, E; Wallace, A J; Lalloo, F; Newman, W G; Evans, D G (Journal of medical genetics, 2015)
BackgroundDespite classification of the BRCA2c.9976A>T, p.(Lys3326Ter) variant as a polymorphism, it has been associated with increased risks of pancreatic, lung, oesophageal and breast cancer.MethodsWe have noticed multiple co-occurrences of the BRCA2 c.9976A>T variant with the pathogenic BRCA2c.6275_6276delTT frameshift mutation p.(Leu2092ProfsTer7) and using a cohort study have assessed if this might account for these tumour risk associations.ResultsWe identified 52 families with BRCA2c.6275_6276delTT, all of which occur in cis with the BRCA2c.9976A>T variant allele as demonstrated by co-segregation in all family members tested. Of 3245 breast/ovarian cancer samples sequenced for BRCA2, only 43/3245 (1.3%) carried BRCA2 c.9976A>T alone, after excluding individuals with BRCA2c.6275_6276delTT (n=22) or other BRCA1 (n=3) or BRCA2 (n=2) pathogenic mutations. The resultant frequency (1.3%) after removal of co-occurring mutations is lower than the 1.7% and 1.67% frequencies from two control populations for BRCA2 c.9976A>T, but similar to the 1.39% seen in the Exome Aggregation Consortium database. We did not identify increased frequencies of oesophageal, pancreatic or lung cancer in families with just BRCA2 c.9976A>T using person-years at risk analysis.ConclusionsIt is likely that the previous associations of increased cancer risks due to BRCA2c.9976A>T represent reporting bias and are contributed to because the variant is in LD with BRCA2c.6275_6276delTT.